Carbonaceous aerosol source apportionment and assessment of transport-related pollution. (15th June 2022) - Minderytė, Agnė; Pauraite, Julija; Dudoitis, Vadimas; Plauškaitė, Kristina; Kilikevičius, Artūras; Matijošius, Jonas; Rimkus, Alfredas; Kilikevičienė, Kristina; Vainorius, Darius; Byčenkienė, Steigvilė
Abstract: Diesel vehicles are one of many sources of black carbon (BC) emissions in Europe; nevertheless, due to recent changes in fuel composition towards renewable fuel such as biodiesel, advances in engine design and pollution control technology, BC and organic carbon (OC) emissions may worsen air quality and encourage global warming. As there are no regulatory terms on BC mass concentration levels, assessment of pollution sources is crucial for air quality improvement policies and mitigation of climate change. BC mass concentration and aerosol optical absorption were derived using 7-wavelenght Aethalometer during 3 measurement campaigns in 2014, 2017, and 2020. BC source apportionment analysis was performed using 18 combinations of absorption Ångström exponent (AAE) values for assessing BC to fossil fuel combustion and biomass burning. The choice of the most suitable AAE combination (0.9 and 2.2, respectively) was supported by organic aerosol (OA) source apportionment results. AAE value for transport exhaust emission (0.95) from locally available diesel fuel was established using (CI) 1.9 TDI engine with different engine torque regimes and 7-wavelenght Aethalometer. Statistically and experimentally obtained values were compared and showed great agreement. Subsequently, a statistically obtained AAEtr value was used for BC source apportionment and long-term analysis. A significant increase in the contribution of transport-related BC contribution was observed between years 2014 and 2020 (from 51% to 65%) which was associated with a boost in the use of diesel vehicles (by 83.9% of diesel passenger cars comparing 2014 and 2020) and growing diesel fuel consumption. These findings underline the diesel transport-induced problem for local air quality together with its impact on atmospheric radiative balance and raise concerns for public health. Highlights: The choice of AAE combination was supported by OA source apportionment results. BC source apportionment revealed increasing trend of transport-related pollution. A significant increase in BCtr light absorption was observed during 2014–2020.